Managing budget cuts in Edinburgh's sport and recreation services: progressive localism in a resilient local authority?. Issue 1 (2nd January 2018) - Reid, Gavin
ABSTRACT: While the Westminster government's class-driven austerity is UK-wide, Scottish social democracy influences how it is conceptualised and resisted. The Scottish Parliament's limited devolved powers and a broken system of local government funding – with roots in both Scottish and Westminster Governments – leaves little room for challenging austerity. Responding to increased demand for services and financial constraints, Edinburgh Council's 'transformation programme' sought a leaner, agile council to promote community resilience. As a discretionary service, protected by a weak legislative requirement, sport received significant cuts. Using interviews with policy actors, this article contends that, by embracing the conservative concept of resilience over the more critical concept of resourcefulness, the council's management of cuts revolved around financial savings and income generation not socially just progressive localism. The leisure trust's success in managing cuts encouraged more, mirroring the argument that, in resilient councils, councillors think the 'outer organisation' can be diminished without damaging the core. This accelerated neoliberal processes pre-dating austerity. Apparent progressive localism from asset transfers downplays how, driven by financial savings, this empowered some middle-class individuals while deflecting attention from the state's withdrawal from promoting social justice. A campaign to save a leisure pool in a deprived area saw arguments for an ethical 'play' space to support community resilience. However, within neoliberalism's 'cracks and fissures', protestors encouraged council support for community management – later rescinded amidst much acrimony – for a facility they could never run progressively.